2018
DOI: 10.21577/0103-5053.20180020
|View full text |Cite
|
Sign up to set email alerts
|

An Environmentally Friendly Procedure to Obtain Flavonoids From Brazilian Citrus Waste

Abstract: Currently, most food waste is used as animal feed and this process does not take advantage of the available chemical composition. A Brazilian example is the citrus fruit processing wastes (CFPW), which have begun to draw attention due to their biological importance. In order to access the main compounds of this matrix, an efficient and environmentally friendly procedure was tested. From this extract, flavonoids as naringenin, hesperitin, chrysoeriol, sinensetin, 3,5,6,7,3',4'-hexamethoxyflavone, nobiletin, 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…The extraction method developed was inexpensive and the flavonoids could be obtained on a large scale. 18 Citrus fruit extract including hesperidin, sinensetin, and other flavonoids displayed promising in vitro antioxidant, antidiabetic, and antibacterial activities. It was suggested that consumption of the entire fruit, rather than its single compounds, may be more beneficial for health due to the complex mixture of compounds' interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The extraction method developed was inexpensive and the flavonoids could be obtained on a large scale. 18 Citrus fruit extract including hesperidin, sinensetin, and other flavonoids displayed promising in vitro antioxidant, antidiabetic, and antibacterial activities. It was suggested that consumption of the entire fruit, rather than its single compounds, may be more beneficial for health due to the complex mixture of compounds' interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The orange production scenario in São Paulo shows great potential as a citrus-based biorefinery, and our research group, in collaboration with local industries and institutions from Brazil and abroad, has developed concepts and applications for such biorefineries. , As a result, this can be considered a good example of cooperation toward chemical innovation in the orange supply chain, established together with Fundecitrus, citrus farmers, and processing companies. , …”
mentioning
confidence: 99%
“…11 The orange production scenario in Saõ Paulo shows great potential as a citrus-based biorefinery, and our research group, in collaboration with local industries and institutions from Brazil and abroad, has developed concepts and applications for such biorefineries. 12,13 As a result, this can be considered a good example of cooperation toward chemical innovation in the orange supply chain, established together with Fundecitrus, citrus farmers, and processing companies. 14,15 The teaching practice focused on orange production and processing in the state of Saõ Paulo, Brazil, as a base for developing a guided investigative laboratory practice on extracting valuable products from orange waste, incorporating GS chemistry concepts and methods.…”
mentioning
confidence: 99%
“…Generally, a single-stage extraction cannot meet these conditions, and a repeated (multistage) extraction is used . In many cases, large amounts of solvents are needed in multistage extractions and the yields of bioactive products obtained are low . One of the goals to increase the extraction yield is raising the solvent capacity to dissolve the compound of interest by changing temperature or mixing solvents.…”
Section: Introductionmentioning
confidence: 99%
“…44 In many cases, large amounts of solvents are needed in multistage extractions and the yields of bioactive products obtained are low. 45 One of the goals to increase the extraction yield is raising the solvent capacity to dissolve the compound of interest by changing temperature or mixing solvents. Extraction yield of any substance depends on solubility; therefore, the choice of solvents used in extraction experiments must be performed according to the analyte's physical− chemical properties.…”
Section: ■ Introductionmentioning
confidence: 99%